Skills Required for Mathematics Faculty Members to conduct Research in Math Education - Hafedh Taher, Dr. Nedhal Abdul (International Journal of Advanced Science and Technology, 2019)
The study identifies the required research skills formathematics faculty members to conduct research in math education, moreover it identifies which aspects of research skills are more required, so it aims to develop a list of research skills for any training program, to identify the extent of required skillsand to identify if there are significant differences in the extent of the required skills for faculty members, and among the universities. The researcher used the analytical descriptive method in the collection, classification and processing of the data for this study. Based on the monitoring of many theoretical and empirical studies the researcher prepared a list of the research skills, a questionnaire designed for collecting data allocated on six dimensions. The validity and reliability of the questionnaire were checked. The study sample was chosen randomly. The Statistical Package for Social Sciences (SPSS) was used for the processing of the studies data.